Pengaruh Gaya Kepemimpinan, Motivasi, dan Budaya Organisasi Terhadap Kinerja Karyawan Mata Hati Coffee Shop - Puspitasari, Jefi; Kadeni, Kadeni (Ecobuss, 2024)
The purpose of this study was to determine the effect of leadership style, motivation, and organizational culture on employee performance at Mata Hati Coffee Shop. The population used is all employees totaling 52 people spread across three (3) branches of Mata Hati Coffee Shop. The sampling technique uses a type of non-probability sampling, namely saturated samples. The research method uses quantitative research methods. The results of this study found that there is a positive and significant influence between leadership style on the performance of Mata Hati Coffee Shop employees partially. there is a positive and significant influence between motivation on the performance of Mata Hati Coffee Shop employees partially. there is a positive and significant influence between organizational culture on the performance of Mata Hati Coffee Shop employees partially. There is an influence between leadership style, motivation, and organizational culture on the performance of Mata Hati Coffee Shop employees simultaneously